Prenatal Education Planning in the Perspective of the Qur'an: Perencanaan Pendidikan Pranatal dalam Perspektif Al-Qur’an - Imam Wilujeng; Eni Fariyatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2021)
Islam more than 14 centuries ago has laid the foundations of prenatal education. This can be seen through Allah’s intructions in the Qur’an surah Ali Imran verses35 and 41. In verse 35 Allah SWT gives intuctions on how the wife should do when pregnant. And in verse 41 explains how a husband should do when he finds out that his wife is pregnant. The method used in this research is literature study (library research), namely by way reviewing books, literature, notes, Qur’anic verses and interpretations related to the problem to be solved. Among the research results are the pregnant wife represents the child she is carrying, carrying out activities in accordance with what she aspires to. While her husband always increases dhikir to Allah so that it makes the atmosphere of the household calm and conducive, which in turn will have a good effect on the life of the child in his wife’s womb. So prenatal education is very urgent in delivering good and quality servants of God.